Incapacidades decorrentes de acidentes de trânsito em Mato Grosso, 2014 - Oliveira, Yorinne Sayuri Hatakeyama (2018)
At latest decades, the traffic accidents have become an important public health problem in Brazil and in the world. The main data sources used in order to study this disease (morbidity and mortality) only recorded the outcomes of severe or fatal cases. Therefore, it has a few knowledge about victim’s health condition after discharge from hospital or outpatient clinic, possible consequences and disabilities. Objective. To analyze incapacities in victims of traffic accidents that were attended at emergency and emergency units in the state of Mato Grosso. Methodology. A cross-sectional study that analyzed the databases of the survey "Accidents and Violence: Knowing Non-fatal Events and Their Consequences", of a subsample (N = 345) it was submitted to two instruments: VIVA-survey and a questionnaire based on International Classification of Functioning, Disability and Health (CIF). The study population comprises victims of traffic accidents treated in emergency and emergency units in 13 municipalities in Mato Grosso. For this study, the sociodemographic and accident-related variables and the "disability" variable of interest were correlated - for which, two categories were adopted: “yes and no”. A bivariate analysis was performed using Prevalence Ratio (PR) with its Confidence Interval (95% CI) and the chi-square (x2) test of Pearson, and multivariate analysis of multiple Poisson regression model with robust variance. Results. The majority of accidents occurred in males (64,9%), their ages were between 20 and 39 years (61,2%), these victims were motorcyclists (83,5%), they were elementary and middle school students (87,9%), and these races were black or brown (64,3%). Considering multivariate analysis, disability was significantly associated with variables age, body part, surgery and hospitalization. The main functional deficiencies were sensory and pain (47,8%) and musculoskeletal and movement related (46,0%); and structural deficiencies related to the movement (85,5%). In activity and participation, limitations were predominantly related to mobility (41,4%). The presence of barriers in services, systems and policies evidenced a 22.0% greater prevalence of disabilities than in the presence of facilitators. Conclusion. The study showed the magnitude of the main disabilities and associated factors in victims of traffic accidents. The use of the CIF and the proposed methodology fills a gap in the literature on this aggravation.